Ekofeminisme dalam Puisi-Puisi Perempuan Indonesia: Kajian Stilistika dan Ekokritik - Lestari, Riana Dwi; Aeni, Eli Syarifah (Aksara, 2025)
Poetry serves as a medium for women to express critical perspectives on the relationship between the female body and nature, both of which are subjected to oppression, especially amidst environmental crises and gender inequality. Female poets such as Oka Rusmini, Dorothea Rosa Herliany, and Toeti Heraty have written poetry that is not only personal but also acts as a form of protest against patriarchy and anthropocentric worldviews that neglect the environment. Therefore, this research is important to explore how women's poetry symbolically and ideologically portrays the body, trauma, love, and nature, as well as how poetic language is used to voice social, ecological, and feminist critiques. This study employs two approaches: stylistics and ecofeminist ecocriticism. The stylistic approach examines the linguistic aspects of poetry, such as diction, imagery, figurative language, and sound structure, which create aesthetic and emotional effects. Meanwhile, the ecofeminist ecocritical approach analyzes the relationship between representations of the female body and nature as a whole within the poems. Three poems are analyzed in this study: the untitled poem by Oka Rusmini (beginning with the line “Pertemuan itu, jadi benih pulau…”), “Nikah Sungai” by Dorothea Rosa Herliany, and “Lukisan Wanita 1938” by Toeti Heraty. This research uses a descriptive qualitative methodology and applies literary text analysis techniques. The analysis process begins with a close reading of the three poems. Stylistic elements are identified, and symbolic meanings are interpreted using the ecofeminist ecocritical framework. The findings reveal that the female body is depicted as an ecological and historical landscape marked by wounds and oppression. The poems expose systems of power that oppress both women and nature, while offering a space for resistance through symbols of nature, the body, and death. These poems explicitly reject the romanticization of love, the aestheticization of the body, and historical narratives that silence women's voices. AbstrakPuisi menjadi media bagi perempuan untuk menyampaikan pandangan kritis tentang hubungan antara tubuh perempuan dan alam yang mengalami penindasan, terutama di tengah krisis lingkungan dan ketidakadilan gender. Penyair perempuan seperti Oka Rusmini, Dorothea Rosa Herliany, dan Toeti Heraty telah menulis puisi yang tidak hanya bersifat pribadi, tetapi juga sebagai bentuk protes terhadap patriarki dan cara pandang manusia yang mengabaikan alam (antroposentrisme). Karena itu, penelitian ini penting untuk melihat puisi-puisi perempuan menggambarkan tubuh, trauma, cinta, dan alam secara simbolis dan ideologis, serta bagaimana bahasa puisi digunakan untuk menyampaikan kritik sosial, lingkungan, dan feminisme. Penelitian ini menggunakan dua pendekatan: stilistika dan ekokritik-ekofeminisme. Pendekatan stilistika melihat aspek kebahasaan puisi, seperti diksi, citraan, gaya bahasa, dan struktur bunyi yang memberikan dampak estetis dan emosional. Sementara itu, pendekatan ekokritik-ekofeminisme melihat hubungan antara representasi tubuh perempuan dan alam secara keseluruhan dalam puisi. Puisi tanpa judul karya Oka Rusmini (dengan kutipan pembuka "Pertemuan itu, jadi benih pulau.), "Nikah Sungai" karya Dorothea Rosa Herliany, dan "Lukisan Wanita 1938" karya Toeti Heraty adalah ketiga puisi yang dianalisis. Penelitian ini menggunakan metodologi kualitatif deskriptif dan menggunakan teknik analisis teks sastra. Proses analisis dimulai dengan pembacaan menyeluruh dari ketiga puisi. Stilistika diidentifikasi dan makna simbolik ditafsirkan menggunakan kerangka ekokritik-ekofeminisme. Hasil penelitian menunjukkan bahwa tubuh perempuan digambarkan sebagai lanskap ekologis dan historis yang dipenuhi dengan luka dan penindasan. Puisi membongkar kekuasaan yang menindas alam dan perempuan dan menawarkan ruang perlawanan melalui simbol alam, tubuh, dan kematian. Puisi-puisi ini secara khusus menentang romantisasi cinta, estetika tubuh, dan narasi sejarah yang mengabaikan suara perempuan.